A new joining by forming process to produce lap joints in metal sheets - Pragana, João (2018)
This paper proposes a new joining by forming process to produce lap joints in metal sheets. The process combines partial cutting and bending with mechanical interlocking by sheet-bulk compression of tabs in the direction perpendicular to thickness. The lap joints are flat with all the plastically deforming material contained within the thickness of the two sheets partially placed over one another. The design of the lap joints is performed by a simple analytical model and the overall concept is validated by means of numerical modelling and experimentation. Destructive shear tests demonstrate the effectiveness and performance of the new proposed lap joints. (C) 2018 Published by Elsevier Ltd on behalf of CIRP.